No effect of carbohydrate feeding on 16 km cycling time trial performance - Jeukendrup, A. E.; Hopkins, S.; Aragon-Vargas, L. F.; Hulston, C. (European Journal of Applied Physiology, 2008)
The aim of this study is to investigate the effects of CHO ingestion during high intensity exercise performance lasting approximately 25 min. Twelve endurance trained male cyclists (age 19-41 years; body mass 73.2 ± 4.2 kg; VO2max 66.4 ± 6.2 ml/kgmin) completed a simulated 16 km time trial (457 ± 37 kJ) time trial in the lab on three occasions. Once they received a 6% carbohydrate electrolyte solution (CHO) and twice they received the same electrolyte containing placebo drink (PLA). Carbohydrate or placebo drinks were ingested 5 min before the start (4 ml kg-1) and at 25, 50, and 75% of completion of the time trial (1.4 ml kg-1). The CHO drink was a 6% sucrose-glucose-electrolyte solution. No differences were observed in the time to complete the time trials with either treatment. Time in min:s were 25:30 ± 1:34 and 25:27 ± 1:46 for the two placebo trials and 25:38 ± 1:59 in the CHO trial. Power output during the time trials was also remarkably similar: 300 ± 37 W, 301 ± 39 W and 299 ± 40 W, respectively. Pacing strategies and heart rate were identical in all three trials. From the two placebo trials, a coefficient of variation for this performance task was calculated to be 1.1%. Data from this study provides evidence that carbohydrate ingestion during short high intensity exercise (~30 min, 85-90% VO2max) does not improve performance. Furthermore, this study found a very low coefficient of variation (1.1%) for a simulated 16 km time trial.